Adoption of Protective Behaviours: Residents Response to City Smog in Hefei, China. (27th January 2017) - Cheng, Peng; Wei, Jiuchang; Marinova, Dora; Guo, Xiumei
Abstract : City smog outbreaks in many Chinese cities aroused public concern about health risks and environmental pollution in China. This study investigates protective behaviours of the citizens in response to city smog using protective action decision to understand their actions. A survey was conducted in Hefei, Anhui in 2015, after the city experienced severe smog events. The data from 429 respondents supported the developed model. Hazard‐related attributes were the strongest predictors for willingness to adopt protective behaviours. Public risk perception only positively affected self‐protective actions. Information sources affected risk perception and increased the respondents' self‐protective intentions. Older adults and respondents with lower educational levels were more likely to adopt environmentally friendly actions. The findings' theoretical and practical implications are also discussed.